Fabrication of starch-based emulsion gel beads by an inverse gelation technique for loading proanthocyanidin and curcumin. (April 2023) - Bu, Xiaotong; Guan, Minghang; Dai, Lei; Ji, Na; Qin, Yang; Xu, Xingfeng; Xiong, Liu; Shi, Rui; Sun, Qingjie
Abstract: In this study, large-scale emulsion gel beads were fabricated using an inverse emulsion gelation technique. Gelation was achieved by simple starch retrogradation, which enabled dual loading of proanthocyanidin and curcumin. The properties and morphologies of the fabricated emulsion gel beads were characterized by means of laser particle size analysis, rheological measurement, texture profile analysis, optical microscopy, and scanning electron microscopy. The average size of the emulsion gel beads ranged from 2.8 to 5.9 mm. With the increase in the starch concentration from 9.1% to 33.3%, the hardness of the gel beads was increased 8.8-fold, from 195.31 ± 30.73 g to 1734.94 ± 155.17 g, whereas the swelling ratio of the beads showed a decreasing trend under different treatment conditions (pH range from 1.5 to 12 and temperature range from 25 to 80 °C). Increasing the starch concentration from 9.1% to 33.3% also resulted in a decrease in the release ratio of proanthocyanidins and curcumin from 68.32% to 16.66% and from 7.00% to 0.45%, respectively, after simulated gastric ﬂuid digestion for 2 h, indicating that starch-based emulsion gel beads can tolerate the damage imposed by the gastric environment. Disruption of the starch gel network by amylase hydrolysis and digestion in simulated intestinal fluid for 4 h caused a cumulative release of proanthocyanidins and curcumin from the beads in excess of 75% and 28%, respectively. Therefore, starch-based emulsion gel beads, which combine the advantages of emulsion and hydrogel systems, are ideal carriers for loading hydrophilic and hydrophobic active ingredients. Graphical abstract: Image 1 Highlights: Emulsion gel beads were fabricated using an inverse emulsion gelation technique. The starch-based gel beads enable dual loading of proanthocyanidin and curcumin. The beads can protect active ingredients to be delivered to the intestinal tract.